2017
DOI: 10.3389/fmicb.2016.02123
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Hot Springs in Central India Reveals Hydrocarbon Degrading Thermophiles and Pathways Essential for Survival in Extreme Environments

Abstract: Extreme ecosystems such as hot springs are of great interest as a source of novel extremophilic species, enzymes, metabolic functions for survival and biotechnological products. India harbors hundreds of hot springs, the majority of which are not yet explored and require comprehensive studies to unravel their unknown and untapped phylogenetic and functional diversity. The aim of this study was to perform a large-scale metagenomic analysis of three major hot springs located in central India namely, Badi Anhoni,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 71 publications
9
61
0
Order By: Relevance
“…A study comparing metagenomes obtained from cold and hot deserts found thermophiles having a higher number of genes involved in metabolism and transport of carbohydrates and secondary metabolites (Le et al 2016) . Similar results were found in other studies of metagenomes from hot springs in India, where abundance of KEGG (Ogata et al 1999;Kanehisa et al 2017) pathways was investigated (Badhai, Ghosh, and Das 2015;Saxena et al 2016) .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study comparing metagenomes obtained from cold and hot deserts found thermophiles having a higher number of genes involved in metabolism and transport of carbohydrates and secondary metabolites (Le et al 2016) . Similar results were found in other studies of metagenomes from hot springs in India, where abundance of KEGG (Ogata et al 1999;Kanehisa et al 2017) pathways was investigated (Badhai, Ghosh, and Das 2015;Saxena et al 2016) .…”
Section: Introductionsupporting
confidence: 89%
“…Of the eight KEGG pathways -with significant over-representation of enzymes changing with temperature -four were previously identified as over-represented in metagenomic studies of high temperature habitats (Badhai, Ghosh, and Das 2015;Saxena et al 2016) : carbon fixation pathway in prokaryotes, pyruvate metabolism, methane metabolism and purine metabolism. The TCA cycle, another enriched KEGG pathway, is known to be extensively utilized in three thermophilic bacteria (Cordova et al 2017) .…”
Section: Discussionmentioning
confidence: 99%
“…While constituting only 21.35% and 5.9% of bacterial sequences in the CA and BV mat, respectively , Pseudomonas has also been reported in thermal springs in India where, importantly, the presence of Pseudomonas stutzeri and Acidovorax spp. was linked to the possible presence of genes associated with hydrocarbon degradation pathways in the Anhoni hot springs (43.5–55°C) (Saxena et al., ). Presumptively, this implies that thermal springs are potential reservoirs of bacterial species that can be used in the bioremediation of polluted environments.…”
Section: Resultsmentioning
confidence: 99%
“…The following groups of thermophiles are commonly suggested based on their optimal growth temperature: moderate thermophiles growing between 50 and 70°C with an optimum of 55-65°C, extreme thermophiles growing optimally at temperatures between 65 and 80°C, and hyperthermophiles with Correspondence: Dr. Margarita Kambourova (margikam@ microbio.bas.bg), Institute of Microbiology, Bulgarian Academy of Sciences, Acad. Such compounds significantly contribute to biotechnological advancements in recent years [4][5][6]. 26, 1113 Sofia, Bulgaria Abbreviation: EPSs, exopolysaccharides optimum growth higher than 80°C [3].…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms have developed unique metabolic and physiological capabilities to thrive in extreme habitats and to produce particular metabolites that are rarely present in microbes of modest environments. Such compounds significantly contribute to biotechnological advancements in recent years [4][5][6]. Among compounds involved in thermophilic adaptation, enzymes and exopolysaccharides (EPSs) are of special biotechnological interest due to their unusual stability not only to high temperatures but also to detergents, organic solvents, high salt concentrations.…”
Section: Introductionmentioning
confidence: 99%